BEST QUALITY TOMATO SELECTION BY SUPPLY CHAIN STRATEGY FOR RENEWABLE ENERGY - Thanh Nguyen, Phong; Le Hoang Thuy To Nguyen, Quyen; Hashim, Wahidah; Maseleno, Andino; Susilowati, Tri; Suyono, Suyono; Bich Huynh, Vy Dang; Bich Vu, Ngoc; Phuc Le, Loan; Dang Vo, Khoa; Thanh Phan, Phuong (International Journal of Supply Chain Management, 2019)
World agriculture still faces challenges quite fundamental, it is about the quality issues and the increasing of competitiveness through productivity and the eficiency. This research focused on the criteria of best tomato types and how to apply the Simple Additive weighting method (SAW) into a Decision Support System (DSS) for election best quality tomato that can assist farmers in determining the best type of tomato for renewable energy and supply chain strategy, based on the criteria that have been chosen, such as: tomato size, tomato color, tomato shape and tomato disease. By using the application of Simple Additive weighting method into Decision Support Systems value, it can be concluded that V5 is the best quality tomato and has a predicate value of 83.75 with the fragile values, as follows: 50-69 = Enough, 70-82 = Good, 83-100 = Best.